The sociology of debt - Featherstone, Mark (Bristol : Policy Press, 2019)
Key thinkers with a range of perspectives provide a sociological analysis of debt focused upon its social, political, economic, and cultural meanings. Contributors consider the lived experience of debt and financialisation taking place globally with accounts that span sociological, cultural, and economic forms of analysis.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Debt -- Social aspects